Hook effect: a case study of a giant invasive prolactinoma in pregnancy with falsely low serum prolactin - Nikumbhe, Rahul D.; Kamble, Bhimrao G.; Agarkar, Aniket D.; Khan, Sufiyan A. (International Journal of Research in Medical Sciences, 2025)
Prolactinoma is the most common type of pituitary adenoma characterized by excessive production of the hormone prolactin, while the majority of tumours are benign. A small percentage can develop into more aggressive macro adenocarcinomas, which pose a significant challenge in management and prognosis. High estrogen levels during pregnancy lead to an increase in the size of prolactinomas leading to compression of optic chiasma. Eventually, it manifests as visual symptoms and headaches. Pharmacotherapy with dopamine agonists is the treatment of choice and multidisciplinary management results in successful outcomes. The present study describes A 28-year-old female with a 36-week pregnancy presenting with complaints of neck pain, headache, and blurring of vision to our hospital. On inquiry, the patient gave a history of galactorrhoea so a magnetic resonance imaging (MRI) brain was done. MRI brain was suggestive of a giant 18×9×8 mm macroadenoma.